Peningkatan Value Baliho dengan Pendekatan Short Term Memory pada Baliho Calon Bupati Indragiri Hilir Provinsi Riau - Roberta Zulfhi Surya; Dwi Yuli Prasetyo; Ratna Witasari (Universitas Bunda Mulia, 2017)
Baliho is a thing or media of promotion which is very useful for giving information or activity that relates to public. Moreover, baliho is also to commerce the new product even it is used to the election like the president election, governor and regent to introduce themselves and recognize self to attract public attention. Interesting baliho should have been ease to be remembered by public so memory is very important to be considered in baliho design especially short term memory has the important function in remembering or memorizing. The purpose of this research is to know how much establishment of value baliho and improvement of short term memory which is used value engineering method. This research was conducted in desa sungai bela with 22 samples. The result of this research that uses value engineering counting was increased about 66,06 % and t-test show from desired. The sample is shown the differences between old baliho design with the new design about 66,01% with the average of differences about 1.3246 which is sig (0,000) < α (0.05). So it can be concluded that there is a significant differential in new baliho design.Keywords: Value Baliho, Short Term Memory.